A QUANTITATIVE EVALUATION OF THE RELATIONSHIP BETWEEN FACTORS AFFECTING THE SOCIAL SURVEY RESULTS - A. F. Sokol; R. V. Shurupova (Сеченовский вестник, 2013)
This paper describes additional methods of data analysis of the sociological survey used to solve a variety of research and practical problems in the field of sociology of medicine.